2017
DOI: 10.1038/s41598-017-09840-8
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrated Domain Movement in Catalysis by Cytochrome P450 Reductase

Abstract: NADPH-cytochrome P450 reductase is a multi-domain redox enzyme which is a key component of the P450 mono-oxygenase drug-metabolizing system. We report studies of the conformational equilibrium of this enzyme using small-angle neutron scattering, under conditions where we are able to control the redox state of the enzyme precisely. Different redox states have a profound effect on domain orientation in the enzyme and we analyse the data in terms of a two-state equilibrium between compact and extended conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 76 publications
3
31
1
Order By: Relevance
“…1416, 53 Both the 4-electron reduced NADP + -bound and 4-electron-reduced 2′-AMP-bound wild type structures (above and Rwere et al 32 ) demonstrate a more tightly closed conformation and shorter interflavin distance - consistent with SAXS/SANS solutions studies, which demonstrated a more compact conformation upon NADP + binding. 13,52 In the Asp632Ala mutant structures, Asp632 loop movement occurs even in the presence of bound NADP + or 2′-AMP, and is associated with instability of the mutant crystals. Thus, increased mobility of the flavin domains as a result of increased Asp632 loop movement prevents formation of the closed NADP + -bound conformation required for stable crystal formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1416, 53 Both the 4-electron reduced NADP + -bound and 4-electron-reduced 2′-AMP-bound wild type structures (above and Rwere et al 32 ) demonstrate a more tightly closed conformation and shorter interflavin distance - consistent with SAXS/SANS solutions studies, which demonstrated a more compact conformation upon NADP + binding. 13,52 In the Asp632Ala mutant structures, Asp632 loop movement occurs even in the presence of bound NADP + or 2′-AMP, and is associated with instability of the mutant crystals. Thus, increased mobility of the flavin domains as a result of increased Asp632 loop movement prevents formation of the closed NADP + -bound conformation required for stable crystal formation.…”
Section: Discussionmentioning
confidence: 99%
“…56 However, due to the complexity of the system (technical difficulties involving resolution of spectral overlaps, redox states, and presence or absence of cofactor binding) these studies have achieved only qualitative results. Recent studies by the Roberts group, using SANS 52 methods, showed that only one or two major conformations exist at a given redox state in the presence or absence of NADP(H). Even though the structural resolution is very low, the SANS studies showed that major conformations existing in solution are the CLOSED (as observed in the crystal structure of oxidized wild type enzyme), OPEN (observed in the structure of ΔTGEE CYPOR), or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…). The mechanism by which CPR transfers electrons to partner proteins is complex and evidence suggests this is achieved through conformational sampling of CPR by relative reorganization of cofactor‐binding protein domains .…”
Section: Introductionmentioning
confidence: 99%
“…The differences between mutant and wt CPR forms investigated here were located in the cofactor‐binding domain of the FAD, remote from the predicted interaction surface of CPR and P450 . Thus, pronounced form‐specific effects of mutations on the ability to support P450 catalysis were unexpected since the FAD domain is not thought to interact directly with the P450 .…”
Section: Resultsmentioning
confidence: 82%
“…To interact with a P450, CPR needs to be in an open conformation, that is, to undergo a large conformational change which gates inter‐flavin electron transfer . Mounting evidence exists that conformational changes are linked to cofactor binding and release, both of which occur at the FAD domain, where the mutations were introduced . Hence, the mutations introduced in the present study may affect domain movement and hence intra‐ and inter‐protein electron transfer.…”
Section: Resultsmentioning
confidence: 95%